Interpersonal arguing in Malaysia and how it compares to the U.S., India, and China - Waheed, Moniza (Marsland Press, 2019)
Malaysia is a nation of 30 million people living in an ethnically and religiously diverse society. Interpersonal arguing, an inherent feature of personal and public experience, seems never to have been previously studied in Malaysia. We did so here and compared results to those obtained in India, China, and the U.S. (where our theories and instruments originated). In Study 1 (N = 230), we found interesting distinctions between Malaysia and the other nations on several measures fundamental to the study of interpersonal arguing. Malaysians had a number of comparatively aggressive impulses, but these were tempered by their higher expectation of civility in arguments and their greater sophistication about the general nature of interpersonal disagreement. Malaysians had positive (not negative) correlations between argument-approach and argument-avoid, and between verbal aggressiveness (prosocial) and verbal aggressiveness (antisocial). Malaysia also produced very few sex differences. In Study 2 (N = 200), we recorded the language of the questionnaires disseminated (English or Bahasa Melayu) and replicated Study 1. Results were largely similar to those from Study 1. We found that age, sex, and the language of the questionnaires did not affect the results. Some unexpected findings for Malaysia showed that there is a discrepancy in the understanding of interpersonal arguing between the countries included in this study and that U.S.-developed theories may not be necessarily applicable in Malaysia, particularly in the case of conflict personalization.